2023
DOI: 10.1039/d3mh00042g
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-triggered in situ gelation with ROS-controlled drug release for cartilage repair

Shunli Wu,
Hao Zhang,
Sicheng Wang
et al.

Abstract: Cartilage defects are usually caused by acute trauma and chronic degeneration. However, it is still a great challenge to improve the repair of articular cartilage defects due to the limited...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 48 publications
(76 reference statements)
1
15
0
Order By: Relevance
“…5 A depicted experimental animals were randomly allocated to four different groups: Sham group (serving as the positive control), Control group (untreated experimental group), RSD-MS group (group treated solely with RSD-MSs), and COP group (group treated with COPs). Throughout the experimental procedure, at postoperative weeks 5 and 10, rats underwent euthanasia, following which tissue specimens from the femur, heart, liver, kidney, lung, and spleen were harvested for subsequent laboratory analyses [ 33 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…5 A depicted experimental animals were randomly allocated to four different groups: Sham group (serving as the positive control), Control group (untreated experimental group), RSD-MS group (group treated solely with RSD-MSs), and COP group (group treated with COPs). Throughout the experimental procedure, at postoperative weeks 5 and 10, rats underwent euthanasia, following which tissue specimens from the femur, heart, liver, kidney, lung, and spleen were harvested for subsequent laboratory analyses [ 33 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…The analysis results were consistent with our previous findings, indicating that the dual-network DNA–SF hydrogel upregulated the mTOR pathway to promote chondrogenic differentiation of BMSCs. 41 It is worth noting that the DNA–SF hydrogel upregulated ECM receptor interactions and multiple chondrogenic related signaling pathways. As shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Fibrinogen is the natural biological polymer that acts as a scaffold for tissue regeneration and promotes cell migration, as well as the good biocompatibility. Fibrin hydrogel formed by the mixture of fibrinogen and thrombin is known as a cell adhesive extracellular matrix, which has been widely applied in regenerative medicine. Nakamura et al successfully printed living cells mixed in fibrin hydrogels to form active hydrogel sheets. They also observed that cells in fibrin hydrogel adhered, expanded, and proliferated during incubation .…”
Section: Introductionmentioning
confidence: 99%